Developing Business Start-up to Promote Job Creation: An Entrepreneurship Perspective in Pandemic Era - Sartono, Sartono; Hermawan, Iwan; Amid, Jusmi; Suwondo, Agus; Putri, Devani Nariratya (JDM (Jurnal Dinamika Manajemen), 2023)
Market stagnation and employee rationalization caused by global social restrictions are problems arising from the Pandemic crisis. It caused a 6.5% increase in the global unemployment rate in 2020 and pushed down the work opportunity for the labor force. Therefore, the state needs efforts to increase the availability of job opportunities by supporting the formation of a start-up. This study aims to form a strategic model with Start-up entrepreneurship as a driver in increasing job opportunities in the Pandemic Era. This study refers data panel from GEM (Global Entrepreneurship Monitor) in 2019-2021 with 102 data from 34 countries. The testing method used is the Component-Based Structural Equation Model (CB-SEM), which shows that the Start-up Entrepreneurship variable has succeeded in becoming a total mediation variable for the relationship between Entrepreneurship Capability and Job Creation Activity and the relationship between Entrepreneurship Intention and Job Creation Activity. This study provides a body of knowledge on applying the management Labor Supply theory. The significance of the role of Entrepreneurship capability, which emphasizes a proactive attitude in creating opportunities and entrepreneurship intention through business incubation, can increase Start-up Entrepreneurship, which impacts Job Creation Activity.